CLEC4M and STXBP5 gene variations contribute to von Willebrand factor level variation in von Willebrand disease. (9th May 2015) - Sanders, Y. V.; van der Bom, J. G.; Isaacs, A.; Cnossen, M. H.; de Maat, M. P. M.; Laros‐van Gorkom, B. A. P.; Fijnvandraat, K.; Meijer, K.; van Duijn, C. M.; Mauser‐Bunschoten, E. P.; Eikenboom, J.; Leebeek, F. W. G.; et al.
Summary Background von Willebrand factor (VWF) levels in healthy individuals are influenced by variations in genetic loci other than the VWF gene, whose contribution to VWF levels in patients with von Willebrand disease (VWD) is largely unknown. Objectives To investigate the association between single‐nucleotide polymorphisms (SNPs), VWF levels, and bleeding phenotype. Patients/Methods In 364 type 1 VWD and 240 type 2 VWD patients from the nationwide cross‐sectional 'Willebrand in The Netherlands' (WiN) study, we studied the association between eight SNPs in STXBP5, SCARA5, ABO, VWF, STAB2, STX2, TC2N, and CLEC4M, and VWF antigen (VWF:Ag), VWF activity (VWF:Act), and bleeding phenotype as assessed with the Tosetto bleeding score. Results In type 1 patients, STXBP5 was associated with a lower VWF:Ag level (adjusted difference of −3.0 IU dL−1 per allele; 95% confidence interval [CI] −6.0 to 0.1) and CLEC4M with both a lower VWF:Ag level (−4.3 IU dL−1 per allele; 95% CI −7.9 to −0.6) and lower VWF:Act (−5.7 IU dL−1 per allele; 95% CI −10.9 to −0.5). In type 2 patients, none of the SNPs was associated with VWF levels. None of the genetic variants was associated with bleeding score. Conclusions Genetic variations in STXBP5 and CLEC4M are associated with VWF level variation in type 1 VWD, but not in type 2 VWD. This study increases our understanding of the pathophysiology of VWD, and provides a further indication of the involvement of STXBP5 and CLEC4M in determining VWF levels in VWD.